Predicting Bankruptcy of Agriculture Companies: Validating Selected Models - Karas, Michal; Režňáková, Mária; Pokorný, Petr (Faculty of Management, Czestochowa University of Technology, 2017)
Many bankruptcy prediction models have been published so far, most of them were especially designated for the manufacturing companies. According to several studies, these models are inappropriate for other industries, as such application would be connected with a significantly lower accuracy than could be expected. The aim of this paper is to analyse the current accuracy of four traditional bankruptcy prediction models in the field of agriculture. The results showed that these models are less accurate in this field in comparison with the original results. This motivates the effort of deriving new models that would be specially developed for agriculture business.

Many bankruptcy prediction models have been published so far, most of them were especially designated for the manufacturing companies. According to several studies, these models are inappropriate for other industries, as such application would be connected with a significantly lower accuracy than could be expected. The aim of this paper is to analyse the current accuracy of four traditional bankruptcy prediction models in the field of agriculture. The results showed that these models are less accurate in this field in comparison with the original results. This motivates the effort of deriving new models that would be specially developed for agriculture business.
Predicting Bankruptcy of Agriculture Companies: Validating Selected Models
Keywords: bankruptcy prediction models; ROC curves; agriculture; bankruptcy prediction models; ROC curves; agriculture